Peculiarities of Stress and Coping among Public Prosecutors: Data from Two Studies - Valickas, Gintautas; Vanagaitė, Kristina (Teisė, 2019)
The article analyzes work-related stress experienced by Lithuanian prosecutors (349 and 274 prosecutors participated in the study in 2013 in 2017, respectively), its main sources, and the coping strategies used by the prosecutors. It also delves into the relations of stress, coping strategies, and prosecutors’ sociodemographic characteristics; the paper presents a comparison of data gathered in 2013 and 2017.